Slovenska izseljenska zgodovina kot del slovenske nacionalne zgodovine - Klemenčič, Matjaž (Zgodovinski časopis, 1998)
The author treats Slovene immigrant history as an integral part of the Slovene national history. He defines as emigrants all who emigrated from the Slovene ethnic territories regardless of the numerous changes of state boundaries during the course of history. He definess the images of America as seen by potential Slovene emigrants and determines the size of Slovene immigrant groups in different countries during different phases of emigration. The author divides the history of Slovene emigrants after their settling in the new homelands into the history of the activities of their special organisations, which were established to preserve their ethnic identity (freternal benefit societies, ethnic Catholic parishes and Slovene national homes) and the history of their political activities related to the events in the old homeland. The author also treats political activities of the Slovene immigrants and their descendants in elections on municipal, county, state and national levels
Keywords: socialna zgodovina; Amerika; slovenski izseljenci; zgodovinski pregledi